Minimal Associations Between Clinical Data and Children's Self-Reported Health-Related Quality of Life in Children With Chronic Conditions—A Cross-Sectional Study - Fischer, Kathrin I.; Barthel, Dana; Otto, Christiane; Ravens-Sieberer, Ulrike; Thyen, Ute; Klein, Marcus; Walter, Otto; Rose, Matthias; Nolte, Sandra (Frontiers in Pediatrics, 2019)
Introduction: The improvement – or at least maintenance – of health-related quality of life (HRQoL) in children and adolescents is one of the main aims of chronic disease care. This study examines HRQoL of children and adolescents with three different chronic conditions (i.e., diabetes mellitus, asthma, juvenile arthritis) using the newly developed computer-adaptive test Kids-CAT, comprising five HRQoL domains: physical well-being, psychological well-being, parent relations, social support and peers, and school well-being. Further, associations between HRQoL and distinct clinical data and medical assessments are investigated to explore how much variability of the five domains can be explained by these variables. Methods: Cross-sectional data of the Kids-CAT study were analyzed. The Kids-CAT was used in two outpatient clinics in northern Germany gathering data on self-reported HRQoL in n= 309 children and adolescents aged 7-17 years. Additionally, general patient information, clinical data, and pediatrician-reported medical assessments were measured. Multiple regression analyses were conducted to explore associations between HRQoL and selected variables (i.e., disease duration, co-morbidity, disease control, overall health status). Results: Overall, self-reported HRQoL in all five domains were comparable to data of an age- and sex-matched reference population. Results of regression analyses indicated that the investigated variables only minimally explain variance in the five Kids-CAT domains. Sociodemographic, clinical data, and medical assessments explained 18.4% of the variance in physical well-being, 10.7% in psychological well-being, and <10% of the variance in parent relations, social support and peers, and school well-being. Conclusion: Sociodemographic data, disease duration, co-morbidity, and medical assessments, such as disease control or pediatrician-assessed overall health status show low association with HRQoL of children and adolescents with chronic conditions. Our results indicate that these variables are not suitable to draw any conclusions about children’s HRQoL, which is especially true for psychological and social well-being. Hence, data on self-reported HRQoL delivers crucial additional information on children’s well-being and can improve healthcare professionals’ understanding of the subjective well-being of their young patients. The implementation of tools like the Kids-CAT can facilitate the identification of potential problem areas, which should enable healthcare professionals to better address specific healthcare needs.